Die Bezeichnung der Daemonen im Bulgarischen - Dukova, Ute (Specimina philologiae Slavicae, 1997)
The present investigation has grown directly out of etymological practice and is committed to the traditional historical-comparative etymological method. Moreover, it stands in the scientific context of the directions that consider Slavic mythology as the object of study of linguistics, especially the Tartu and Moscow School and the Russian and Polish ethnolinguistics. She works on dialectal material that is difficult to access from a relatively unexplored region of the Slavia and suggests a number of new etymological solutions. The study of a compact lexical-semantic group allows the names to be stratified according to their relative chronology and, on the other hand, to illuminate inner relationships and semantic processes on a diachronic and synchronous level.